Assessment of the validity of orthopantomographs in the evaluation of mandibular steepness in Libya - Tayisir Ganeiber; Iman Bugaighis (Wolters Kluwer Medknow Publications, 2018)
AIM: The value of gonial angle indicates the range of steepness as well as the direction of mandibular growth. Exact measurement of right (R) and left (L) gonial angles from a lateral cephalometric radiograph is challenging due to the superimposition of both sides. Thus, the aim of the present study was to assess the potential of determining accurate measurement of R and L gonial angles by employing orthopantomographs (OPGs) and to compare the findings with the measurements obtained from lateral cephalometric radiographs. MATERIALS AND METHODS: A total of 125 standardized panoramic as well as lateral cephalometric radiographs of Libyan subjects were obtained from the orthodontic clinical records (36 males and 89 females). Mandibular inclination was computed by averaging the R and L gonial angles produced by drawing tangents to the inferior border of the mandible and to the distal aspect of the ascending ramus and the condylon on each OPG. Moreover, similar steps were followed to extract the gonial angle from the cephalometric radiographs. RESULTS: Student's paired t-tests revealed no significant discrepancies between the R and L gonial angle values extracted from the OPG (123.88° ± 6.53° and 123.27° ± 6.55°) at P = 0.0.070. The mean values of the gonial angle (average of the R and L mean values) extracted from the OPG (123.58° ± 6.38°) and cephalometric radiographs (125.14° ± 6.23°) were not significantly different (P = 0.084). Furthermore, Pearson's correlation coefficient revealed strong correlation between the value of the gonial angle measured in the cephalometric radiograph and the mean value extracted from the OPG (r = 0.897 at P < 0.001). CONCLUSION: OPGs are as useful as lateral cephalometric radiographs in the assessment of mandibular inclination and steepness in Libyan subjects. They have the added advantage of reducing patient exposure to radiation by cutting the number of radiographs required during diagnosis.